SANKSI PIDANA PLAGIARISME DALAM HUKUM POSITIF DI INDONESIA - Hulman Panjaitan (Fakultas Hukum Universitas Kristen Indonesia, 2017)
Abstract One of the norms that must be obeyed by everyone when writing a scientific literature is to mention the source of citation and other people’s opinion, this has been acknowledged among academics especially in universities, the most fundamental fact is, many writers do not pay attention to this matter or they do it intentionally, if this matter is done, then this action is called plagiarism and the person who performs the action is called a plagiarist, in regard to this matter, the law regulates the matter by imposing a criminal threat. Keyword: Sanksi Pidana Plagiarisme